In situ Analysis of Coral Recruits Using Fluorescence Imaging - Zweifler, Adi; Akkaynak, Derya; Mass, Tali; Treibitz, Tali (Frontiers in Marine Science, 2017)
Recruitment is a fundamental process that inﬂuences coral population dynamics as well as reef community structure. To date, coral recruitment success rates are poorly quantified because survey methods are labor-intensive and require manual interpretation. Thus, they are prone to human errors and have low repeatability - a gap we aim to bridge in this research. Since both corals and their symbiotic algae contain fluorescent pigments (chlorophyll and fluorescent proteins), we used the non-invasive Fluorescence Imaging System (FluorIS) and developed a methodology to acquire daytime fluorescent photographs and identify coral recruits in them. We tested our method by monitoring twenty random quadrats at two sites in the Gulf of Aqaba, Israel. The quadrats were surveyed once a month for eight months in order to track the settlement, mortality and survival rates of new coral recruits. We demonstrate daytime imaging using our method and identification of coral recruits as small as 1 mm in diameter, in a 20 x 20 cm quadrat. Our results show that this photographic method reduces surveyor errors and improves precision. The surveys revealed that on average, there are ~2 new coral recruit settlements (<2cm) for a quadrat (40cm2) per month and that 83% of them survive the first month. Our study suggests a relative stability in the Gulf of Aqaba coral population during the survey period. The ability to survey recruits during the day using low-cost, easy-to-use photographic equipment has the potential to contribute significantly to the standardization of coral reef monitoring and management tools, at a time when the world’s coral reefs are declining due to local and global stressors.